ANALISA PENGARUH PENGGUNAAN CONTROLLER PADA FILTER AKTIF SHUNT TERHADAP PEREDAMAN DISTORSI HARMONISA - I Made Suartika; I Wayan Rinas (Jurnal SPEKTRUM, 2020)
The types of filters used to reduce harmonic distortion are passive filters, active filtersand hybrid filters. The type of filter that usually uses the system controller is an active filter. Inthis study, an analysis of current harmonic distortion from the simulation results using matlabhaccording to the IEEE Std 519-1992 standard in existing conditions, active filter operatingconditions, active filter operation using PID controllers and active filters based on Fuzzy LogicController. The simulation results of the three models used show that the resulting THDii stillmeets the IEEE Std 519-1992 standard, namely the THDi is still 8%, the simulation results forPID-based active filters are: pasa R = 2.89%; S = 2.34%; T = 3.23% and based on fuzzy logiccontrollers are: R = 0.15%; S = 0.11%; T = 0.13%.